Water Content, Physical Quality of Seeds and Post-Harvest Fungal Attacks on Peanuts - Miladiarsi, Miladiarsi; Tsaniyah, Barokati; Putri, Riska Awalia; Saputra, Hiksa Maulana; Sianturi, Yosua Pangihutan Pardamean Alextio (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The decline in peanut seed quality can result from improper post-harvest handling, including drying, pod peeling, and storage, which can damage the seeds and reduce their quality. Damaged seeds and high water content facilitate fungal growth on peanuts. Maintaining and ensuring peanut quality during market storage is very important. This study aims to examine the relationship between air content, the percentage of damaged seeds, and the percentage of seeds infected by post-harvest fungal species in peanut seeds. The experimental method involved measuring air content with a DELMHORST Model G-7 Moisture Meter. The physical quality of seeds was assessed based on the percentages of intact, wrinkled, and damaged seeds. To determine the percentage of seeds infected with fungi, the direct planting method was used, employing Dichloran 18% Glycerol Agar (DG18+) media. The results indicated that each sample’s air content was within the normal range of 8-9%, but the physical quality of the seeds was 59.7%, associated with fungal attacks by species including Aspergillus flavus, A. niger, A. tamari, Fusarium semitechtum, Mucor sp., Eurotium repens, and E. chevalieri. These findings suggest that air content and seed damage influence fungal diversity, providing valuable insights for maintaining peanut seed quality during the post-harvest process until they reach the market.